عقیدہ ختم نبوت ازروئے احادیث مع قادیانی مغالطوں کاازالہ: The Believe in the Finality of Prophethood According to the Hadiths and the Correction of the Qadiani Fallacies - Kashif Ali; Dr. Faridah Yousuf (Al Manhal Research Journal, 2023)
The belief in the finality of prophethood is the most important and fundamental belief of Islam. The entire edifice of the religion of islam is based on this belief. It has been openly declared in more than a hundred verses of the Holy Qur'an that the Prophet, peace and blessings be upon him, is the last prophet and messenger until the Resurrection. It is to be remembered that the first consensus of this ummah was that the claim of prophethood is death and death is obligatory, and the ummah has followed this first consensus until today and has maintained this tradition. In the last century, intellectuals and intellectuals worked continuously to make the Muslim Ummah aware of the reality of Qadianism.Because One of the problems facing the Muslim Ummah is Qadianism The Qadianis are misguiding the Muslims by giving wrong interpretations of the Hadiths. In this article,these wrong interpretations have been accounted for.So that Muslims can protect their faith. Finally Suggestions and recommendations have also been presented.